Pengembangan Sistem Informasi Terpadu Industri Pariwisata Kota Batam Menerapkan User Centered Design Berbasis Website (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The Integrated Tourism Industry System in Batam City is a system designed to make it easier for tourists to find tourism information in the city of Batam. Batam City is one of the cities with leading tourist destinations that are in great demand by domestic and foreign tourists. However, the lack of promotion and tourism information in Batam City is an obstacle for tourists to get this information. This integrated tourism information system is equipped with a cost estimation feature that makes it easier for tourists to check the estimated cost to be issued and what destinations are available in each tourist destination. Coupled with the event calendar menu, tourists can see what activities will be held in the city of Batam, and on the main page of the tourism website tourists can see a description of the city of Batam as well as a gallery containing pictures of Batam city tourism. This Integrated Tourism Industry System in Batam City is based on a website using the CodeIgniter framework, php as the basis for the programming language, and for data storage using mysql, and xampp is used as the server. This system is expected in the future to become the main media for tourism promotion in the city of Batam, so that tourism in the city of Batam is able to compete with tours in other cities, this will have an impact on both the industrial and business sectors because they have utilized and followed the development of information technology.